Projeto conceitual de interpretação ambiental para a gruta dos Paiva Parque Estadual Intervales (SP) - Oliveira, Maria Sinária Laveredo de (2023)
Environmental Interpretation (IA) constitutes a set of technical, artistic and philosophical procedures, applied in order to propose the revelation of meanings, instead of simply communicating information, aiming to establish a transformative relationship between the public and the protected heritage. In this context, the present work presents a conceptual AI project proposal for the Gruta dos Paiva, located in the buffer zone of the Intervales State Park (PEI), in the State of São Paulo. The project was designed to contribute to the implementation of conservation management strategies, as the cave is one of PEI's tourist attractions. The research was developed through a systematic literature review, adaptations of the ROVUC method for field activities, interviews, dialogues and participatory seminars. The results presented correspond to a base of interpretative means, considering the attractive potential of each point of interest studied. The study presents information for more detailed discussions on proposals and standards for materials and graphic solutions, itineraries, content and interpretive panels arranged on the trails, in Gruta dos Paiva and its surroundings, through suggested routing, with the insertion of a geological itinerary, animated production for graphic representation in the audio visual hall, installation of sensory spaces to ensure local accessibility, installation of interpretive panels and personalized itinerary for the karst route.